1986
DOI: 10.2307/3430384
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Activity of Disinfection By-Products

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Investigations involving the potential of ozone for producing mutagenic activity however are much less consistent, with reported levels ranging from those as high as for chlorination to virtually non-existent (Dolara et al, 1981;van der Gaag et al, 1982;Zoetemann et al, 1982;Bourbigot et al, 1983;Duguet et al, 1983;Meier and Bull, 1985;Cognet et al, 1985;Bourbigot et al, 1986). Studies which have incorporated granular activated carbon (GAC) filtration following disinfection have demonstrated that mutagenicity has usually been eliminated following this step (Bourbigot et al, 1983;van Hoof, 1983;Kruithof et al, 1985;Cognet et al, 1985;Bourbigot et al, 1986) and in some cases could not be detected even following TOC breakthrough (Monarca et al, 1983;Loper et al, 1985).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Investigations involving the potential of ozone for producing mutagenic activity however are much less consistent, with reported levels ranging from those as high as for chlorination to virtually non-existent (Dolara et al, 1981;van der Gaag et al, 1982;Zoetemann et al, 1982;Bourbigot et al, 1983;Duguet et al, 1983;Meier and Bull, 1985;Cognet et al, 1985;Bourbigot et al, 1986). Studies which have incorporated granular activated carbon (GAC) filtration following disinfection have demonstrated that mutagenicity has usually been eliminated following this step (Bourbigot et al, 1983;van Hoof, 1983;Kruithof et al, 1985;Cognet et al, 1985;Bourbigot et al, 1986) and in some cases could not be detected even following TOC breakthrough (Monarca et al, 1983;Loper et al, 1985).…”
Section: Introductionmentioning
confidence: 95%
“…Studies which have incorporated granular activated carbon (GAC) filtration following disinfection have demonstrated that mutagenicity has usually been eliminated following this step (Bourbigot et al, 1983;van Hoof, 1983;Kruithof et al, 1985;Cognet et al, 1985;Bourbigot et al, 1986) and in some cases could not be detected even following TOC breakthrough (Monarca et al, 1983;Loper et al, 1985).…”
Section: Introductionmentioning
confidence: 97%
“…Its decomposition products (hydroxyl free radicals) have an oxidant power superior to ozone itself, and in addition, it appears to form a much smaller amount of mutagens than either chlorine or its derivatives (3)(4)(5). On the other hand, ozonization of surface water containing organic substances (especially fulvic and humic acids), has been demonstrated to produce low molecular weight carbonyl compounds (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 98%
“…Traditional drinking water treatment technologies, both physical and chemical, can successfully remove these pollutants; however, they also have limitations, such as the production of high levels of genotoxic byproducts [6,7]. Many researchers have demonstrated that the use of biological processes in drinking water treatment has many advantages over conventional alternatives, including high water recoveries, low operation cost and limited byproduct formation [8].…”
Section: Introductionmentioning
confidence: 99%